Neoplasia of aortic intima. Issue 6 (November 1964) - Sladden, R. A.
Abstract : Two cases of arterial obstruction, in the region of the aortic bifurcation, are described. In both cases, cellular proliferation of neoplastic type was found to be causing the obstruction, and in one case small embolic metastases were found in the lower limbs and lungs. No primary tumour was found in any site other than the aortic intima itself. Two apparently similar cases have been reported in recent years. It is suggested that this condition, although probably very rare, may be overlooked for several reasons unless obstructive aortic lesions are examined histologically as a routine.